2018
DOI: 10.1111/ejh.13004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerance of GELOXD/P‐GEMOXD in newly diagnosed nasal‐type extranodal NK/T‐cell lymphoma: A multicenter retrospective study

Abstract: The GELOXD and P-GEMOXD chemotherapy regimens are well tolerated and provide favorable survival outcomes in patients with ENKTCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…Our results support previous observations that the baseline SUVmax correlates with prognosis in ENKTCL [35]. The PINK score represents a new model used to predict outcomes in ENKTCL patients treated with non-anthracycline-based therapies, and this model was con rmed in subsequent studies [7,36]. Our research assessed the impact of the PINK on prognosis and found that a high PINK score was associated with a worse outcome.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results support previous observations that the baseline SUVmax correlates with prognosis in ENKTCL [35]. The PINK score represents a new model used to predict outcomes in ENKTCL patients treated with non-anthracycline-based therapies, and this model was con rmed in subsequent studies [7,36]. Our research assessed the impact of the PINK on prognosis and found that a high PINK score was associated with a worse outcome.…”
Section: Discussionsupporting
confidence: 89%
“…As lymphoma cells lack L-asparagine synthetase and are unable to synthesize the essential amino acid asparagine, Lasparaginase and Peg can exert anticancer effects by hydrolyzing serum asparagines in ENKTCL patients. Some Lasp/Peg based regimens such as GELOXD, SMILE and DDGP have been developed in the last decade and have been proven to be effective in ENKTCL patients [1,7,23]. In this study, L/P-VIPD resulted in excellent survival outcomes, with 5year PFS and 5-year OS rates of 73.6% and 88.7%, respectively, consistent with the results of a previous study [8].…”
Section: Discussionsupporting
confidence: 88%
“…We named this new treatment the SVILE regimen. Our control regimen was based on the commonly used PemOx/GELOX 26 , which has a positive effect on ENKTL. PemOx/GELOX treatment consists of pegaspargase, gemcitabine, and oxaliplatin, and is denoted P-GemOx.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a CR rate of patients with early ENKTL after GELOX sandwich chemoradiation of 74%, and a total efficacy rate of 96%, values comparable to the results of our study. Li et al 26 , in a retrospective multicenter study, have reported that the CR rate after treatment with gemcitabine, oxaliplatin, L-asparaginase, and dexamethasone (GELOXD)/gemcitabine, oxaliplatin, pegaspargase, and dexamethasone (P-GEMOXD) for patients with ND-ENKTL is 83%. In another retrospective study, the ORR and CR rates of patients with ND-ENKTL in stage I/II after receiving P-GEMOX sandwich chemoradiation have been found to be 94.3% and 80.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Normal cells can avoid death by synthesizing sufficient endogenous asparagine through asparagine synthetase [ 12 ]. Currently, regimens of GELOX (gemcitabine, oxaliplatin, L-asparaginase/pegaspargase) [ 13 ], SMILE (dexamethasone, methotrexate, ifosfamide, L-asparaginase/pegaspargase, etoposide) [ 14 ], VLP (vincristine, L-asparaginase/pegaspargase, prednisone) [ 15 ], VIDL (etoposide, ifosfamide, dexamethasone, L-asparaginase/pegaspargase) [ 16 ], and MIDLE (methotrexate, ifosfamide, dexamethasone, L-asparaginase/pegaspargase, etoposide) [ 17 ] are proven to be effective to treat ENKTL. The treatment modalities of early-stage ENKTL include concurrent, sequential, and “sandwich” chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%